Formulasi Dan Evaluasi Sediaan Serum Gel Ekstrak Bunga Melati (Jasminum sambac L.): Formulasi Dan Evaluasi Sediaan Serum Gel Ekstrak Bunga Melati (Jasminum sambac L.) - Siti Malahayati; Dyan Fitri Nugraha; Fitria Noor Hikmah (LPPM Universitas Sari Mulia, 2023)
Background: Serum has high concentration but low viscosity. A facial serum that has a fairly good absorption ability on the skin, the release of the serum's active substances is good and easy to apply on the face. Jasmine flowers contain ingredients that can inhibit staphylococcus epidermidis bacteria and shigella flexneri bacteria with a concentration of 12% which is one of the bacteria that can cause acne. Objectives: To determine the appropriate formulation of the jasmine (jasminum sambac L.) serum gel preparation and to determine the effect of variations in the concentration of hydroxyethyl celullose on the physical evaluation of the (jasminum sambac L.) jasmine flower extract serum gel formulation. Methods: The research used was a quasi-experimental with varying concentrations of hydroxyethyl cellulose 1 gram,2 gram, and 2.5 gram. Serum gel was evaluated for organoleptic physical, homogeneity, spreadability, dry time, adhesion, pH, and viscosity. Result: The results of the observations on the viscous liquid organoleptic test and the homogeneity test of homogeneous preparations. The results of the most optimal dispersion test were formulation 1, the most optimal dry time was formulation 1. The results of the most optimal adhesion test were formulation 1, the most optimal pH test results were formula 2, and the viscosity test all entered the optimal criteria. Conclusion: The most optimal jasmine flower extract serum gel is formulation 1, with a concentration of 1 gram.